Mast cells in the human carotid body. Issue 1 (January 1987) - Heath, D; Lowe, P; Smith, P
Abstract : Mast cell counts were carried out on sections of human carotid bodies from 39 subjects showing one of four stages of histological change associated with aging, and in five subjects showing different forms of histopathology in the carotid body associated with disease. There was no relation between mast cell density and age or the histological changes associated with aging of glomic tissue. The normal range of mast cell density calculated in terms of the 80% confidence limits was 18.5 to 67.5/mm2. In three middle aged subjects with carotid bodies of normal histological appearance there was an abnormally high density of 83 to 96/mm2. In two elderly subjects showing age changes of fibrosis and accumulation of lymphocytes there was an abnormally low density of 12/mm2 or less. Mast cell density was not related to different types of carotid body hyperplasia. The mast cells were essentially stromal in location, usually closely applied to the walls of small glomic blood vessels, and were rarely found in intimate association with glomic chief cells. This suggests that mast cells are not directly concerned with the functions of glomic cells but does not preclude the possibility that they may have some effect on regulating glomic blood vessels and thus participate in the distribution of blood supply within the carotid body.